The Role of Towns and Baths in Community Life And - Khatamova Durdona Madamiovna; Kasimov Ilkhom Maripovich (PT ANTIS International Publisher, 2024)
This article examines the characteristics of the formation and development of the bathhouse art. The brief history, construction process, architectural solutions, and some healing properties of the baths, which are one of the monuments of ancient architecture, are also covered. The conducted long-term scientific research was prepared by visiting and examining these monuments several times and relying on the scientific sources of scientists in the field.